PENGARUH AKSES PAJAK, FASILITAS, KUALITAS PELAYANAN DAN PERSEPSI ADANYA REWARD TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Kurniawan, Asep; Sarlina, Leni; Umiyati, Indah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This study aims to determine the effect of access to taxes, facilities, service quality and perceptions of the existence of rewards for taxpayer compliance registered at SAMSAT Subang. This study uses descriptive quantitative method using primary data. Data collection techniques are questionnaires and literature studies. The population in this study were all motor vehicle taxpayers registered at SAMSAT Subang, and samples in this study were 187 respondents. Hypothesis testing uses multiple linear analysis. The results of this study indicate that access to tax, service quality and perceptions of reward have a positive effect on taxpayer compliance. Whereas facilities do not affect motor vehicle taxpayer compliance.